Determinants of health-related quality of life in Crohn's disease: A systematic review and meta-analysis. (1st February 2014) - van der Have, Mike; van der Aalst, Karen S.; Kaptein, Ad A.; Leenders, Max; Siersema, Peter D.; Oldenburg, Bas; Fidder, Herma H.
Abstract: Background and aims: Understanding the determinants of Crohn's disease (CD) patients' health-related quality of life (HRQOL) may facilitate interventions that improve HRQOL. Therefore, we systematically assessed determinants of HRQOL in adult CD patients. Methods: The databases PubMed, EMBASE, the Cochrane Library, PsycINFO and CINAHL were searched for English abstracts, related to socio-demographic, psychological, clinical and treatment-related determinants of HRQOL in CD disease. Two independent reviewers extracted study characteristics and assessed the methodological quality according the criteria of Hayden et al. The main outcome was the number of studies showing a statistically significant association between the above-mentioned determinants and HRQOL. A meta-analysis was performed to quantify the relationship between disease activity and HRQOL. Results: Of the 2060 articles identified, 29 eligible studies were included. The majority of studies were cross-sectional and had a moderate to high quality. Data on psychological determinants were scarce. Work disability, increased disease activity, number of relapses, corticosteroid treatment and hospitalization rate were significantly associated with a lower HRQOL in the majority of included studies. Biological treatment positively influenced HRQOL. The pooled data on the association between disease activity and HRQOL resulted in a weighed mean correlation coefficient of − 0.61 (CI − 0.65 to − 0.57). Conclusions: HRQOL of adult CD patients is consistently determined by markers of active disease, including work disability, increased disease activity, number of relapses, biological treatment and hospitalization rate. As disease activity contributed to only 37% of HRQOL, there remains a need for additional, possibly modifiable, determinants. These determinants may refine possibilities to improve HRQOL.